Aqua vitae : a history of the saloons and hotel bars of Victoria, 1851-1917 - Mofford, Glen, 1954-2022 (TouchWood Editions, 2016)
"A rowdy, rollicking popular history that celebrates the tales of Victoria's drinking establishments in their heyday. From the raunchy saloons that lined Victoria's notorious Johnson street to the lavish high-class hotel-bars like the Driard and the Empress, Aqua Vitae is a collection of fascinating true stories from the days of swinging doors, smoky bars, and five-cent beers. Read about how the quick actions of an employee of the Bee-hive saloon saved a young Emily Carr from possible death. Discover the gruesome secret uncovered by a startled worker who was prying up the floorboards of the Omineca saloon. And find out about the grisly murder of Mike Powers, the proprietor of the Garrick's Head, a pub that still does a thriving business today. Carefully researched and accompanied by 70+ archival photos, Aqua Vitae covers the time from the first saloon appeared in Victoria in 1851 to 1917 when prohibition shut the party down."--